Survey of mineral oil hydrocarbons in Chinese commercial complementary foods for infants and young children. Issue 9 (2nd September 2021) - Liu, Lingling; Li, Bingning; Yang, Daoyuan; Ouyang, Jie; Sui, Haixia; Wu, Yanwen
ABSTRACT: Recently, mineral oil hydrocarbons (MOH) in various foods have raised significant concern, especially for infants and young children due to their potential adverse health effects. Two fractions can be distinguished by certain analytical techniques, mineral oil saturated hydrocarbons (MOSH) and mineral oil aromatic hydrocarbons (MOAH). The toxicological profile of MOSH and MOAH differs greatly. The toxicity of MOSH is linked with long-term accumulation of some hydrocarbons. MOAH with three to seven, non- or simple-alkylated, aromatic rings may be mutagenic and carcinogenic. However, data on the occurrence of mineral oils in commercial complementary foods for infants and young children are lacking in China. In the present study, 100 commercial food samples were collected, including 26 pureed or paste canned foods, 21 high-protein ground cereal foods (rice flour), 25 raw cereal foods (noodles), and 28 cereal-based molar sticks and biscuits. The content of MOSH and MOAH in those samples was determined by optimised sample preparation methods combined with on-line high-performance liquid chromatography coupled with gas chromatography and flame ionisation detector (HPLC-GC-FID), with a limit of quantification of 0.5 mg/kg. The results indicated that there were no MOAH detected in any of the foods, but MOSH and polyolefin oligomeric saturated hydrocarbons (POSH) existed in most of the food samples, at <0.5–23.68 mg/kg. Moreover, the data and chromatograms of the MOSH and POSH also indicated that these contaminants were closely correlated to their ingredients and manufacturers. The current study provides basic data to understand MOH exposure and consequent health impact. Graphical abstract: uf0001